The Shift of a Surau to Be a Mushalla as a Non-Formal Education Implementation in The Regency of West Sumatra Agam - Ahmad Sabri; Sermal Sermal; Syukra Vadhillah; Atqo Akmal; Sarah Pilbahri (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2022)
The concept of